PENGARUH KUALITAS JASA DAN KEPERCAYAAN TERHADAP KEPUASAN NASABAH Studi pada nasabah pengguna mobile banking PT. Bank Rakyat Indonesia Cabang Semarang Pandanaran - Diona Agela Astari Putri; Wahyu Hidayat (Jurnal Ilmu Administrasi Bisnis, 2017)
Customer satisfaction is determined by the quality of service and trust in the service. Desired by customers, so that quality assurance becomes the key quality for a company and customer trust becomes important in improving transaction service in Bank. Bank BRI is one of the banks that utilize banking facilities contained in the mobile phone to provide one convenience to customers and is a distinctive feature. BRI named their banking services products under the name of BRI mobile banking.This study aims to determine the effect of service quality and trust on customer satisfaction BRI mobile banking Branch Office Semarang Pandanaran Sampling technique using purposive sampling method. The sample in this study amounted to 100 respondents who are users of BRI mobile banking.This study concluded that quality product, service quality and promotion influential positive and significantly to visitor satisfaction. This study concluded that the quality of tourism products, quality of service and promotion of visitor satisfaction, either partially or simultaneously. service quality variables have the greatest influence of other variables. The results obtained by analyzing primary data using validity, reliability test, cross tabulation, correlation coefficient, simple regression analysis, coefficient of determination, significance test (t test) in both directions.As for suggestions that can be given that the security of mobile banking services should be improved so as to reduce the level of login failure and reduce crime in cyberspace.